Differentiated Instruction to Stimulate Multiple Intelligences in Early Childhood Science Learning: A Phenomenological Study in Inclusive Kindergartens - Evi Yulidawati; Diana Diana; Edi Waluyo; Ali Formen (ISEJ : Indonesian Science Education Journal, 2026)
Early childhood science learning in inclusive kindergarten classrooms requires pedagogical practices that are responsive to children's differences in readiness, interests, communication modes, sensory needs, and ways of demonstrating understanding. However, empirical accounts of how teachers translate differentiated instruction into daily science activities while stimulating children's multiple intelligences remain limited. This phenomenological study explored the lived experiences of four kindergarten teachers in implementing differentiated instruction to support early science learning in an inclusive kindergarten. Data were collected through participatory classroom observation, semi-structured interviews, and document analysis of lesson plans, children's learning products, portfolios, and progress notes. The data were analyzed through phenomenological procedures involving repeated reading, horizonalization, meaning-unit coding, clustering of themes, and synthesis of textural and structural descriptions. Five essential themes emerged: responsive planning based on children's interests and needs, multisensory inquiry as process differentiation, flexible representation of learning products, adaptive classroom ecology and peer support, and continuous teacher reflection as real-time pedagogical adjustment. The findings indicate that differentiated science instruction was not implemented as a separate program, but as a dynamic pedagogical stance through which teachers adjusted content, process, product, and learning environment. Multiple intelligences functioned as a practical lens for recognizing children's diverse strengths, while hands-on science activities provided an inclusive space for observation, prediction, classification, questioning, communication, and collaboration. This study contributes to early childhood science education by showing how differentiation, inclusive pedagogy, and multiple-intelligence-oriented learning can be integrated in everyday kindergarten science practices. The findings imply that teacher professional development should move beyond general knowledge of inclusion toward concrete strategies for designing accessible, multisensory, and culturally meaningful science experiences for diverse young learners.